IMPACT OF DIGITAL LEARNING TOOLS ON STUDENT ENGAGEMENT IN ELEMENTARY SCHOOLS - Nadifah, Nadifah; Novita, Mona; Furqan, Moh. (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This study highlights the positive impact of digital learning media on students' academic performance. The analysis shows that the frequency of media usage, the type of media used, and students' perceptions of media effectiveness all have a significant relationship with academic outcomes. The perception of media effectiveness has the strongest correlation (0.55) with a p-value of 0.001, indicating that well-designed media is crucial for supporting student comprehension. These findings confirm Mayer's (2001) multimedia learning theory, emphasizing the importance of verbal and visual elements in learning. Sweller's (1988) cognitive theory suggests that well-designed digital media can reduce cognitive load. The study also emphasizes the role of intrinsic motivation in learning, as described by Deci and Ryan (1985), showing that interactive digital media can enhance students' motivation.Furthermore, adapting technology to local conditions is critical in improving learning outcomes. Therefore, schools in Indonesia need to develop teacher training, adequate infrastructure, and relevant digital content to maximize the benefits of technology in education. This study proposes the implementation of digital media in SD Namira as a model that other schools can adopt to enhance students' academic achievements by integrating technology into the learning process.